Performance Evaluation of U-Tube Pulsating Heat Pipe with Water-Based Nanofluids - Haque, Shahidul; Bin Rashid, Adib; Rhidoy, Taokir Ahmed (European Journal of Applied Sciences, 2022)
The safety and efficiency of electronic equipment are becoming increasingly critical as modern technologies progress significantly. The size of electronic equipment is shrinking as it becomes more integrated. Hence, the heat load per unit area increases, and the standard heat dissipation method may not fulfill their requirements. Therefore, Pulsating Heat Pipe plays an essential role in efficiently removing heat from congested surfaces to satisfy the requirement. To find optimized parameters for a PHP, various investigations are conducted in this work to help performance up-gradation of PHP. As the equipment gets smaller by size and more heat has to be removed from smaller surfaces, nanoparticles can significantly increase heat transfer performance. Furthermore, they can augment the heat transfer ability of fluids inside the PHP by providing capillary wicking, increased thermal effusivity, hydrodynamic instabilities, and structural disjoining pressure. In this work, various experiment is carried out with water-based Aluminum Oxide, Zinc Oxide, and Graphene Oxide Nanofluids. This work will help upgrade PHP’s performance and thus help enhance heat transfer performance from smaller surfaces like Processor of Computers.